Dataset associated with "Genome-wide association analysis of canine T zone lymphoma identifies link to hypothyroidism and a shared association with mast-cell tumors" - Labadie, Julia D.; Elvers, Ingegerd; Spencer Feigelson, Heather; Magzamen, Sheryl; Yoshimoto, Janna; Dossey, Jeremy; Burnett, Robert; Avery, Anne C. (Colorado State University. Libraries, 2020)
Background: T zone lymphoma (TZL), a histologic variant of peripheral T cell lymphoma, represents about 12% of all canine lymphomas. Golden Retrievers appear predisposed, representing over 40% of TZL cases. Prior research found that asymptomatic aged Golden Retrievers frequently have populations of T zone-like cells (phenotypically identical to TZL) of undetermined significance (TZUS), potentially representing a pre-clinical state. These findings suggest a genetic risk factor for this disease and caused us to investigate potential genes of interest. Methods: Privately-owned U.S. Golden Retrievers were categorized as TZL (n=95), TZUS (n=142), or control (n=101) using flow cytometry and genotyped using the Illumina CanineHD BeadChip. Single nucleotide polymorphism (SNP)-specific associations were evaluated using a mixed linear model adjusting for population stratification. Associated regions were subsequently sequenced using a custom sequence capture array (NimbleGen SeqCap EZ Developer Kit) on an Illumina NextSeq 500. Results: We found association with genome-wide significance in regions on chromosomes 8 and 14. The chromosome 14 peak included four SNPs (Odds Ratio=1.18–1.19, p=.3x10-5–5.1x10-5) near three hyaluronidase genes (SPAM1, HYAL4, and HYALP1). Targeted resequencing of this region identified missense mutations in all three genes; the variant in SPAM1 was predicted to be damaging. These mutations were also associated with risk for mast cell tumors among Golden Retrievers in an unrelated study. The chromosome 8 peak contained 7 SNPs (Odds Ratio=1.24–1.42, p= 2.7x10-7–7.5x10-5) near genes involved in thyroid hormone regulation (DIO2 and TSHR). A prior study from our laboratory found hypothyroidism is inversely associated with TZL risk. No coding mutations were found with targeted resequencing but identified variants may play a regulatory role for all or some of the genes. Conclusions: The pathogenesis of canine TZL may be related to hyaluronan breakdown and subsequent production of pro-inflammatory and pro-oncogenic byproducts. The association on chromosome 8 may indicate thyroid hormone is involved in TZL development, consistent with findings from a previous study evaluating epidemiologic risk factors for TZL. Future work is needed to elucidate these mechanisms.
This dataset includes genotyping data for 267 US Golden Retrievers, obtained under CSU IACUC Protocol #13-4473A. Samples were recruited from the privately-owned pet population from October 2013 – May 2015 as part of a larger case-control study with the goal of understanding genetic and environmental risk factors for T zone Lymphoma. Blood samples were genotyped using the Illumina CanineHD BeadChip. Dogs were categorized as case, TZUS, or control. The list of individuals provided has undergone quality control filtering, including: 1) removing dogs with call rates <97.5%, 2) removing dogs of European origin, and 3) removing highly related individuals (half-sibling or closer). For our analysis, we additionally did QC on the SNP dataset, including removing SNPs with call rates <97.5 or minor allele frequency <5%. However, the .bed and .bim files provided are unfiltered.
College of Veterinary Medicine and Biomedical Sciences
Department of Environmental and Radiological Health Sciences
Department of Microbiology, Immunology, and Pathology
Keywords: lymphoma; leukemia; genetics; dog; epidemiology